Triterpenoids from the fruits of Melia azedarach L. and their cytotoxic activities. (September 2022) - Song, Min; Chan, Ging; Lin, Li-Gen; Li, Derong; Zhang, Kehan; Zhang, Xiao-Qi; Ye, Wen-Cai; Li, Na; Zhang, Qing-Wen
Abstract: Eleven undescribed tetracyclic triterpenoids, meliazedarachins A–K, along with twenty-six known compounds were isolated from the fruits of Melia azedarach L.. Their structures were determined by HRESIMS, UV, IR, NMR, X-ray diffraction, electronic circular dichroism (ECD) spectra, and the modified Mosher's method. The cytotoxic activities of all the isolates were measured. Meliazedarachin K and mesendanin N showed cytotoxicity against five human cancer cell lines with IC50 values ranging from 9.02 to 31.31 μ M. Meliazedarachin K showed significant cytotoxicity against HCT116 cell line with IC50 value of 9.02 ± 0.84 μ M. 21 α -methylmelianodiol showed significant cytotoxicity against HCT116 and RKO cell lines with IC50 values of 10.16 ± 1.22 and 8.57 ± 0.80 μ M, respectively. Graphical abstract: Eleven undescribed tetracyclic triterpenoids, meliazedarachins A–K, along with twenty-six known compounds were isolated from the fruits of Melia Azedarach L. Image 1 Highlights: Eleven undescribed tetracyclic triterpenoids were isolated and identified from the fruits of Melia azedarach L.. Their structures were determined by HRESIMS, UV, IR, NMR, X-ray diffraction, ECD, and the modified Mosher's method. Some compounds showed significant cytotoxicity against human cancer cell lines.